The 35mm Solution: Photography, Scientists, and Whales - Nutch, Frank (Qualitative Sociology Review, 2006)
The field technique of photographic identification enabled scientists to individually identify and follow cetacea (whales, dolphins, and porpoises) through their life-cycle. Photographic identification relies on portable, highquality photographic equipment and the naturally occurring markings of individual whales. Being able to identify cetacea individually has enabled scientists to engage in long-term field studies comparable to field studies of land mammals. Further, carrying out long-term field studies has contributed to an exponential growth of scientific knowledge of cetacea and has significantly altered the public’s connection(s) to scientists and cetacea. This article is based on interviews, published material, and observations made by the author at different research settings. It describes how photography and the use of naturally occurring markings of individual cetacea combined to produce photographic identification as a research technique. As a study within the sociology of science and scientific knowledge, this article highlights the emergent character of scientific research; that is, the emergent confluence of cumulative knowledge, theory, method, and empirical observation.